Current strategies to generate mature human induced pluripotent stem cells derived cholangiocytes and future applications. (2nd January 2017) - Cervantes-Alvarez, Eduardo; Wang, Yang; Collin de l'Hortet, Alexandra; Guzman-Lepe, Jorge; Zhu, Jiye; Takeishi, Kazuki
ABSTRACT: Stem cell research has significantly evolved over the last few years, allowing the differentiation of pluripotent cells into almost any kind of lineage possible. Studies that focus on the liver have considerably taken a leap into this novel technology, and hepatocyte-like cells are being generated that are close to resembling actual hepatocytes both genotypically and phenotypically. The potential of this extends from disease models to bioengineering, and even also innovative therapies for end-stage liver disease. Nonetheless, too few attention has been given to the non-parenchymal cells which are also fundamental for normal liver function. This includes cholangiocytes, the cells of the biliary epithelium, without whose role in bile modification and metabolism would impair hepatocyte survival. Such can be observed in diseases that target them, so called cholangiopathies, for which there is much yet to study so as to improve therapeutical options. Protocols that describe the induction of human induced pluripotent stem cells into cholangiocytes are scarce, although progress is being achieved in this area as well. In order to give the current view on this emerging research field, and in hopes to motivate further advances, we present here a review on the known differentiation strategies with sight into future applications.